The impact of knowledge transfer on innovation in multinational corporations: exploring the contingent effects - Nunes, Anne Catherine Lopes Pereira (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics